IDENTIFIKASI BAHAN KELONGSONG PADUAN ZrNbMoGe HASIL UJI HIDRIDASI 400C - 1 JAM MENGGUNAKAN TEKNIK DIFRAKSI = IDENTIFICATION ON ZrNbMoGe ALLOY OF 400C-1 HOUR HYDRIDATION TEST FOR CLADDING MATERIALS BY USING DIFFRACTION TECHNIQUE - Parikin, Parikin; Bandriyana, Bandriyana; Ismoyo, A.H. (Majalah Ilmiah Pengkajian Industri, 2016)
Abstract Synthesis of a new niobium containing zirconium alloy of ZrNbMoGe has been developed in PSTBM-BATAN. In PWR/PHWR reactor, this materials face with liquid coolant i.e. H2O demin that may trig a reaction between hydrogen and containing zirconium. Hydridation tests in argon atmospheer were recently carried out looking for hydrogen effect in material. Hydrogenisation must be avoided due to causing brittle of the material via blistering of Zr-H compound system. Sample with 2%Nb, 0.5%Mo, 0.5%Ge and Zr in balance content has been hydridized by flowing H2 at temperature of 400 oC for an hour. Effects of the test by time-high temperatur dependence on the zirconium content were investigated by X-ray diffractometer. The observed peak at 220.95 was mathematically interpolated by orde-2 polynomial regression. Identifying peak was performed by X-ray diffraction technique and then it conformed ’search and match’ by JCPDS tracing. Results show that new phase in 400oC-1 hour hydridation sample was close to crystal structure of –ZrH2. The crystallographic data emphasize that new phase with lattice parameter of a= b= 3.52 Å and c= 4.45 Å (tetragonal) is (201) plane or 221.60. Also, the JCPDS traces another new orthorhombic phase of Nb3H3O9 at angle of 220.91 with lattice parameter of a= 9.183 Å, b= 22.47 Å and c=4.24 Å conforming to (220) plane. Hypothesized, this is an anti-hydride layer (passivity) that can overcome hydridation process of cladding materials in thereactor. AbstrakSintesis paduan zirkonium yang mengandung unsur Nb (ZrNbMoGe) telah dilakukan di PSTBM-BATAN. Dalam reaktor PWR/PHWR, bahan ini bersentuhan langsung dengan cairan pendingin, yakni: H2O demin yang bisa memicu reaksi antara Hidrogen dan kandungan zirkonium yang reaktif dalam paduan. Uji hidridasi dalam aliran gas H2 beratmosfir gas argon dilaksanakan untuk memprediksi kelakuan paduan ZrNbMoGe pada temperatur tinggi. Peristiwa hidridasi Zr-H sangat dihindari karena peristiwa blistering yang mampu merapuhkan bahan. Sampel paduan dengan kandungan 2%Nb, 0,5%Mo, 0,5%Ge and Zr dalam kesetimbangan telah diuji hidridasi dalam aliran gas H2 pada temperatur 400C selama 1 jam. Pengukuran pola difraksi menggunakan difraktometer sinar-X dengan target Cu. Puncak baru muncul pada sudut 220,95. Interpolasi matematis dilakukan via regresi polinomial orde-2. Identifikasi dan pencocokan profil menggunakan telusuran JCPDS “search and match”. Hasil memperlihatkan bahwa fasa hidridasi (400C-1 jam) sangat dekat dengan struktur kristal –ZrH2. Kristalografi fasa tersebut memiliki parameter kisi a= b= 3,52 Å dan c= 4,45 Å (struktur tetragonal) dengan refleksi pertama bidang (201) pada sudut 221,60. JCPDS juga menampilkan fasa lain berstruktur ortorombik pada sudut 220,91 dengan parameter kisi a= 9,183 Å, b= 22,47 Å and c= 4,24 Å dengan bidang refleksi (220). Fasa ini diduga merupakan lapisan anti-hidrid (passivatif) yang mampu menghalangi penggetasan bahan kelongsong akibat proses hidridisasi dalam reaktor.